A Comparative Study of Parpatadhyarista and Dugdhikadi Yog in The Management of Ashtheela W.S.R. To Benign Prostate Hyperplasia - Gupta, Rajesh; Meena, Tarun (International Research Journal of Ayurveda & Yoga, 2021)
The disease known as benign prostatic hyperplasia (BPH) affects males over the age of 50. Prostate gland is an organ of male reproductive system, that grows significantly biologically throughout fetal development and adolescence. The prostate gland matures towards the end of puberty and remains so until benign Prostatic Hyperplasia occurs, which causes the prostate gland to increase in size and weight after the first five decades of life.The vitiation of Vata Dosha is the primary cause of the diseases listed in Mootraghata. In Samya Avastha, Apana Vata (one of the five kinds of Vata Dosha) is responsible for proper micturition. When the Apana Vata is vitiated, it causes different diseases of the Mutravahasrotas, such as Ashmari, Prameha, Mutraghata, Mutrakrichha, and so on. According to Ayurveda, proper physiological functions can only be achieved when the three Doshas, Vata, Pitta, and Kapha, are in a condition of Samya (equilibrium). Apana Vayu is in charge of Mutravaha Srotas functions. The development of various diseases affecting the Mutravaha Srotas is caused by the vitiation of Apana Vayu. As a result, the concept of treatment for Mutravaha Srotas diseases is to pacify the vitiated Apana Vayu. Shodhana (removal of the vitiated Doshas) and Shamana (pacification of vitiated Doshas by use of oral medicines) are the primary approaches for treating diseases in Ayurvedic literature. Shodhana Chikitsa, as advocated in Ayurvedic Classics, is Vasti therapy for the relief of vitiated Vata Dosha. Oral medications in various forms for Shamana Chikitsa are listed in Ayurvedic Classics.